CHARACTERISTICS AND LONG-TERM OUTCOME OF PATIENTS WITH NONINFECTIOUS RETINAL VASCULITIS. Issue 12 (December 2015) - Shulman, Shiri; Kramer, Michal; Amer, Radgonde; Sorkin, Nir; Schaap-Fogler, Michal; Rosenblatt, Amir; Habot-Wilner, Zohar
Abstract : Purpose: To investigate the characteristics and long-term outcome of patients with noninfectious retinal vasculitis. Methods: This was a retrospective multicenter study. Main outcome measures included patients' characteristics, ocular findings, treatment modalities, and best-corrected visual acuity. All patients had at least 12-month follow-up time. Results: Eighty-two eyes (45 patients) were included. Median follow-up was 46 months (range, 12–210 months). At presentation, 12 of the 45 patients (26.6%) had a known associated systemic or ocular disease. A diagnosis of a new systemic disease was found in additional 14 of 33 patients (42.5%) and birdshot chorioretinopathy in 3 of 33 patients (9.1%). The most common systemic disease was Behcet disease (17/24 patients; 70.8%). Laboratory tests had a low diagnostic value. The most common clinical findings were vitritis (58.5%) and perivascular sheathing (50.5%). Most patients were treated with immunosuppressive medications. Mean best-corrected visual acuity improved significantly during follow-up, patients with Behcet disease and worse visual acuity at baseline were more likely to have visual acuity improvement ( P < 0.001). Conclusion: A new systemic or ocular disease associated with retinal vasculitis was found in more than half of the patients. Behcet disease was the most common newly diagnosed disease. Specific diagnosis leading to proper management is important to maintain favorable long-term visual outcome. Abstract : This study assessed the characteristics and long-term outcome of patients with noninfectious retinal vasculitis in Israel. A new systemic or ocular disease associated with retinal vasculitis was found in more than half of the patients, with Behcet disease being the most common. Most patients had favorable long-term visual outcome.